A ROLE FOR BACTERIAL-DERIVED PROTEASES AND PROTEASE INHIBITORS IN FOOD SENSITIVITY. - McCarville, Justin (My University, 2017)
Celiac disease is a chronic atrophic enteropathy triggered by the ingestion of dietary gluten in genetically predisposed individuals expressing HLA class II genes, DQ2 or DQ8. Both innate and adaptive immune mechanisms are required for the development of the disease. The adaptive immune response is well characterized and includes the development of gluten-specific T-cells and antibodies towards gluten and the autoantigen, tissue transglutaminase 2. Less is known about the initiation of the innate immune response and its triggers, which is characterized by increases in cytokines such as IL-15, leading to proliferation and cytotoxic transformation of intraepithelial lymphocytes that are not specific to gluten. Although genetic susceptibility is necessary for celiac disease and present in 30% of most populations, only about 1% will develop it. This points to additional environmental factors, which could be microbial in origin. Disruptions of the gut microbial ecosystem, termed the intestinal microbiota, have been associated with the development and severity of many gastrointestinal disorders. Indeed, compositional differences in fecal and small intestinal microbiota have been described in patients with active celiac disease compared to healthy controls. This “dysbiosis” includes increases in small intestinal Proteobacteria and reductions in Firmicutes, but mechanistic information is lacking. Our lab has previously demonstrated that patients with active celiac disease have decreased expression of the serine protease inhibitor elafin in the duodenal mucosa, suggesting that proteolytic imbalance from either host or microbial origin, could be important in disease pathogenesis. The aim of this thesis is to study mechanisms through which the intestinal microbiota may contribute to the development of gluten sensitivity. I thus hypothesized that the proteolytic capacity of a dysbiotic small intestinal microbiota could promote the development of gluten sensitivity, in a genetically susceptible host. Firstly, I investigated whether the intestinal microbiota is a source of proteases in the gut lumen, that metabolize gluten in vivo affecting its immunogenicity. Secondly, I studied whether and how bacterial proteases stimulate innate immune mechanisms, relevant to celiac disease pathogenesis. Last, I investigated whether some of these mechanisms could be targeted to improve gluten sensitivity. In Chapter 3 of this thesis, I show that the small intestinal microbiota participates in gluten metabolism in vivo in mice. Proteobacteria and opportunistic pathogen Pseudomonas aeruginosa, isolated from patients with celiac disease, metabolize gluten proteins through microbial elastase. Bacterially-modified gluten peptides translocate the mucosal barrier with efficiency and retain immunostimulatory capacity when incubated with gluten-specific T-cells from patients with celiac disease. However, bacteria found in higher abundance in healthy individuals, such as Lactobacilli, metabolize P. aeruginosa modified gluten peptides reducing their antigenicity. This constitutes an opportunistic pathogen-gluten-host mechanism that could modulate celiac disease risk in genetically susceptible people. In Chapter 4, I show that bacterial proteases capable of extracellularly metabolizing gluten, such as P. aeruginosa elastase, also have the capacity to stimulate innate immune responses in the small intestine, likely through a protease activated receptor-2-dependent mechanism. This innate immune response does not require HLArisk genes and is characterized by non-specific increases in small intestinal intraepithelial lymphocytes. In mice transgenic for the HLA-DQ8 gene, the presence of P. aeruginosa elastase in the small intestine exacerbates gluten-induced pathology. In Chapter 5, I use a commensal Bifidobacterium longum strain that naturally produces a serine protease inhibitor, with the ability to inhibit elastase activity. I show that administration of Bifidobacterium longum to mice expressing the HLA-DQ8 gene prevents gluten immunopathology. The effect is dependent on the production of the bacterial serine protease inhibitor, as it was not observed with a B. longum knock-out for the serine protease inhibitor gene. Within this thesis, I demonstrate that microbial proteases can modulate gluten sensitivity through participation in both adaptive and innate immune pathways using celiac disease as a model of gastrointestinal disease. Further, I provide pre-clinical support that this pathway can be targeted for therapeutic purposes using protease inhibitors from commensal bacterial strains. My results provide causal evidence and novel mechanisms through which small intestinal bacteria may exacerbate or attenuate gluten sensitivity.